Reimplementing English as a Mandatory Subject in Elementary Schools: Teachers’ Beliefs under the Merdeka Curriculum - Arif, Nely; Masbirorotni; Volya, Duti; Heryanti, Reny (Universitas Jambi, Magister Program of English Education Department, 2024)
The re-implementation of English as a compulsory subject at the elementary school (SD) and Madrasah Ibtidayah (MI) levels in the Merdeka Curriculum has caused a debate about its impact on educators and students. This study explores teachers' beliefs regarding this reimplementation and examines both challenges and benefits associated with teaching English at the elementary level. Data were collected using a qualitative approach through interviews with five teachers who are members of the MGMP (Subject Teacher Forum) Rayon 2 under the Ministry of Religious Affairs in Jambi City, Jambi. The findings highlight challenges such as administrative burdens, insufficient training, and resource limitations. However, teaching English early also provides benefits, including better preparation for advanced education and improved linguistic and interpersonal skills. These insights are crucial for policymakers to refine strategies supporting curriculum implementation.